Reconstructing Syntax - Barðdal, Jóhanna; Gildea, Spike; Luján, Eugenio R. (Brill's Studies in Historical Linguistics, 2020)
Contributing to the vigorous discussion of the viability of syntactic reconstruction, this volume offers methods for identifying i) cognates in syntax, and ii) the directionality of syntactic change, thus providing historical syntacticians with evidence that syntactic reconstruction is indeed both theoretically and practically feasible.; Readership: This volume is of interest to all historical syntacticians and historial linguists, as well as to specialists within Indo-European, Semitic, Austronesian and native American languages.